A combined experimental and computational study of the Cu/C (sp2) interface. (July 2021) - You, Xin; Bao, Rui; Zhang, Liangqi; Huang, Xiao; Yi, Jianhong; Hou, Xianghui; Ling, Sanliang
Abstract: Interface optimization is the most important and eternal research issue in preparation of the metal matrix composites (MMCs). For nano sp 2 -carbon material (NSCM)/metal composites, interfacial precipitates are usually formed intentionally or unintentionally, however, the effect of the interface structure and precipitates on the electron transport properties is still unclear, which is especially important for Cu-based material due to the electronic and electrical applications. In this paper, a series of interface models were constructed based on the transmission electron microscopy (TEM) observation of NSCM/Cu composite and calculated through density functional theory (DFT). The geometric structure, interfacial charge transfer, work function, Bader charges, electron differential density distribution and electronic density of states of Cu/graphene (GR), Cu2 O/GR, Cu/Cu2 O and Cu/Cu2 O/GR interfaces were discussed in detail, we conclude that the Cu2 O precipitates at the Cu/GR interface can reduce the average distance and increase the binding energy between Cu and GR. Besides, the formation of Cu2 O can improve the electronic transport between Cu2 O and copper instead of the weak binding of the Cu and graphene, but Schottky barrier at the interface remains an obstacle need to be overcome. The results can provide reference for the interface design of MMCs and the improvement of the composite properties.